1972
DOI: 10.1084/jem.136.1.156
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Allergic Encephalitis

Abstract: The encephalitogenic determinant of brain protein, a nonapeptide having the amino acid sequence Phe-Ser-Trp-Gly-Ala-Glu-Gly-Gln-Lys, has been characterized and synthesized. In a previous study, analogues of this encephalitogenic peptide were synthesized and some were shown to be encephalitogenic while others were not. Guinea pigs were immunized with encephalitogenic peptides having amino acid sequences different from that in the native protein. These guinea pigs did not show cellular immunity in vivo (skin rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1973
1973
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Thus, even when immunized with such a complex antigenic mixture as whole spinal cord, the susceptibility to EAE induction behaves according to predictions based on a single Ir-gene linked to the major histocompatibility locus. The possible existence of Ir-EAE genes in other species would also offer some explanation for nonuniform reactivity among outbred animals tested with various basic protein fraganents (14). The extent to which EAE is a model for human demyelinating diseases such as multiple sclerosis would be strengthened if the correlation of susceptibility and certain HL-A specificities reflects Ir gene participation in the human disease.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, even when immunized with such a complex antigenic mixture as whole spinal cord, the susceptibility to EAE induction behaves according to predictions based on a single Ir-gene linked to the major histocompatibility locus. The possible existence of Ir-EAE genes in other species would also offer some explanation for nonuniform reactivity among outbred animals tested with various basic protein fraganents (14). The extent to which EAE is a model for human demyelinating diseases such as multiple sclerosis would be strengthened if the correlation of susceptibility and certain HL-A specificities reflects Ir gene participation in the human disease.…”
Section: Discussionmentioning
confidence: 99%
“…Here again, these children were not suffering from EAE, MS, or cancer. Finally, Spitler et al (34,35) showed that guinea pigs sensitized with encephalitogenic peptides having amino acid sequences different from that in the test protein did not show cellular immunity in vivo or in vitro to myelin basic protein, although the animals developed EAE. Einstein (6a) showed that antigen (MBP) suppression of EAE in guinea pigs did not require an intact tryptophan, and yet the tryptophan is an absolute requirement for disease induction.…”
Section: Methodsmentioning
confidence: 99%
“…However, the delayed cutaneous hypersensitivity reaction and the release of macrophage slowing factor (as opposed to migration inhibition factor, MIF) are not necessarily linked aspects of the total immune response, as has been noted in studies of other aspects of cellular immunity (Swanborg, 1969;Macfarland and Heilman, 1966;Bergstrand, 1972;Spitler et al, 1972;Bach et al, 1972;Hughes and Paty, 1971).…”
Section: Discussionmentioning
confidence: 98%